Development of the Integrated Worksheet Based on a Field Trip Aves’s Material Topic at Surabaya Zoo to Increase Learning Interest for 10th Grade High School Students - Kotimah, Kusnul; Ambarwati, Reni (Journal of Biology Education, 2020)
Students’ learning interest still needs to be improved, one of the solutions is using the field trip method in a potential learning environment. Surabaya Zoo is a potential learning environment through real objects. The research aimed to produce Integrated Worksheet Based on a Field Trip and describe it’s validity and practicality. This research was developed used 4D models, without the disseminate stage. The development of the worksheet was conducted in September 2019 to May 2020 at the Biology Department of FMIPA Unesa, while validation and practicality data were collected in May 2020. Validation was carried out by three experts, while practicality was collected through respondents consisting of 5 educational practitioners and 22 students of 10th grade high school. The Grasha-Riechmann questionnaire survey was also conducted to determine students' feelings and attitudes through their learning styles. The results showed the validity of the Integrated Worksheet Based on a Field Trip got a score of 4 (very valid) while the practitioner's responses showed the value of mode 4 (very practical) and the results of the students' responses showed an average positive response rate of 91.08% (very good). Based on those results the Integrated Worksheet Based on a Field Trip was declared to be very practical so it’s appropriate to use. The most common learning styles among the students according to the Grasha-Riechmann questionnaire were Participant (45.5%) and Collaborative (31.8%).